The trajectory of C‐reactive protein serum levels in older hip fracture patients with postoperative delirium. (14th May 2019) - Slor, Chantal J.; Witlox, Joost; Adamis, Dimitrios; Jansen, Rene W.M.M.; Houdijk, Alexander P.J.; van Gool, Willem A.; de Jonghe, Jos F.M.; Eikelenboom, Piet
Abstract : Objectives: Important precipitating risk factors for delirium such as infections, vascular disorders, and surgery are accompanied by a systemic inflammatory response. Systemic inflammatory mediators can induce delirium in susceptible individuals. Little is known about the trajectory of systemic inflammatory markers and their role in the development and outcome of delirium. Methods: This is a prospective cohort study of older patients undergoing acute surgery for hip fracture. Baseline characteristics were assessed preoperatively. During hospital admission, presence of delirium was assessed daily according to the Confusion Assessment Method criteria. This study compared the trajectory of serum levels of the C‐reactive protein (CRP) between people with and without postoperative delirium. Blood samples were taken at baseline and at postoperative day 1 through postoperative day 5. Results: Forty‐one out of 121 patients developed postoperative delirium after hip fracture surgery. Longitudinal analysis of the trajectory of serum CRP levels using the Generalized Estimating Equations (GEE) method identified that higher CRP levels were associated with postoperative delirium. CRP levels were higher from postoperative day 2 through postoperative day 5. No significant differences in serum CRP levels were found when we compared patients with short (1‐2 days) and more prolonged delirium (3 days or more). Conclusions: Delirium is associated with an increased systemic inflammatory response, and our results suggest that CRP plays a role in the underlying (inflammatory‐vascular) pathological pathway of postoperative delirium.